Geodynamic evolution of the South Variscan Iberian Suture as recorded by mineral transformations - Figueiras, Jorge (2022)
New structural, petrographic, mineralogical and geochemical data from the Beja-Acebuches Ophiolite Complex (BAOC) are presented, and reviewed together with data published elsewhere. The new data obtained shed light on questions such as: 1) the relative importance of the obduction event; 2) its geological record in the deep levels of BAOC; 3) the nature and intensity of the Variscan metamorphism and deformation during subsequent continental (arc) collision; 4) the age relationships between BAOC and the Beja Igneous Complex; and 5) by means of numerical modelling, the thermal metamorphism of the Ossa-Morena autochthonous terranes induced by the ophiolite obduction. The emerging picture is that of a fairly simple overall geological evolution for BAOC, seamlessly integrated within the evolution of the southern branch of the Iberian Variscides. Obduction of BAOC is a relatively minor early event in the general NE–SW convergence that gave rise to the orogen as seen regionally and is recorded by an anisotropic, high-temperature, metamorphic fabric at the gabbro levels and by subtle features of the chemical composition of primary minerals at the underlying peridotite level; it caused chilling of the obducted ophiolitic slab and no significant metamorphism on the autochtonous rocks of the Ossa-Morena Zone. BAOC underwent most of its deformation and (amphibolite facies) metamorphism during a later collisional event, that took place as the most primitive rocks of the Beja Igneous complex were being intruded, and whose waning stages are responsible for extensive serpentinisation of peridotites and for important aquocarbonic fluid discharges along the semibrittle–brittle shear zones meanwhile developed.